Implementasi Penilaian Aset Tetap Berdasarkan PSAP No. 07: Studi Kasus pada Dinas Pertanian dan Ketahanan Pangan Kota Tarakan - Iqrima Mas Mappangile; Syahrial Maulana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
PSAP or Government Accounting Standard Statement, which is the standard used in government accounting processes. This standard regulates the procedure of recording, reporting and disclosure of the financial transactions of the notice whether it has been in accordance with the applicable accounting principles. The Inid Research aims to find out whether the agricultural and food security services of the city implement fixed asset assessment in accordance with the statements of government accounting standards (PSAP NO. 07). Fearing Highlights, assessments, measurements and disclosure of fixed assets on the financial report (balance). The research method used is descriptive, i.e. how an asset is recognized, assessed, measured and disclosed in the financial report (balance). And From the results of the study, it shows that assessment, Measurement, Confessor, and Disclosure of fixed assets such as land, building, Computer and Other Fixed Assets That Have been As per Researched by the Standing Statement of Accountant Sign 07. This research is expected to increase the transparency and accountability of public financial resources.